La lúdica en el Desarrollo de la Expresión Oral en niños de 4 años de Educación Inicial II, de la Escuela de Educación Básica “Germán Abdo Touma”, de la ciudad de Riobamba. Provincia Chimborazo periodo 2021 - Larrea Quito, Diana Lisseth (2022)
The objective of this research work is to determine the importance of play for the development of oral expression, in children of four years of Initial Education II, of the "Germán Abdo Touma" Basic Education School, in the city of Riobamba. The research is based on the background of previous research and on a referential theoretical framework, which gave sustainability to the work. The thesis work is supported by a type of descriptive, bibliographic and cross-sectional research, with a non-experimental design and a qualitative approach. We worked with a group of four-year-old children from initial education II, the instruments used were observation sheets and a survey addressed to teachers. The investigation was carried out in two moments, the development of oral language was observed prior to the application of ludic activities and after the application, the results obtained indicate the importance of ludic in learning oral expression, taking into account that an average 90% of the children went from an occasional and frequent use of the manifestations of oral expression to a permanent use. It was also determined that teachers have a fairly clear perception of the importance of play in learning oral expression, and integrate strategies and games into their educational processes to motivate students despite the limitations of means and resources.